Comparación de los impactos del estrés sobre los parámetros productivos y reproductivos en la gestación individual y colectiva de hembras porcinas de la granja Villa Alejandra (Timbío, Cauca) (2020)
Porciculture in Colombia has acquired great importance in recent years, being one of the fast-growing species, with the capacity to produce a lot of meat in a very short time and its accelerated reproductive process among others, have been one of the characteristics, that have come to classify it as one of the most important livestock systems in the country. Given the significant growth of this industry, it is planned to carry out a study with the purpose of comparing the impacts of stress on the productive and reproductive parameters of individual and collective gestation in sows. The results of this study revealed that the collective gestation system had significantly (P < 0.05) higher blood cortisol values (82.84±2.3 ng/ml) compared to the individual system (54.05 ± 2.3 ng/ml). In addition, a numeric superiority was obtained in the mortality rate in the collective gestation system (11.8%) in relation to the individual model (6.1%). Similarly, there was a higher average weight of piglets at birth in the individual system (1,335 ± 25.9 g) compared to the group system (1,234 ± 20.0 g) (highly significant differences; P < 0.01).